2017
DOI: 10.1177/0300060517700299
|View full text |Cite
|
Sign up to set email alerts
|

Role of coagulopathy in glucocorticoid-induced osteonecrosis of the femoral head

Abstract: The two major theories of glucocorticoid (GC)-induced osteonecrosis of the femoral head (ONFH) are apoptosis and ischaemia. The traditional theory implicates ischaemia as the main aetiological factor because the final common pathway of ONFH is interruption of blood supply to the bone. The most common causes of interruption of blood supply include fat embolism and coagulation disorders. GCs can directly or indirectly lead to coagulation disorders, producing a hypercoagulable state, followed by poor blood flow, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 76 publications
0
40
0
Order By: Relevance
“…Glucocorticoid (GC) use and alcoholism are associated with avascular necrosis (AVN) of the femoral head, 50% of which leads to collapse and joint destruction within 3 years of diagnosis . The common pathway for ONFH involves interruption of blood supply to the bone, resulting in osteocyte apoptosis and loss of structural integrity, ultimately leading to femoral head collapse . The transplantation of mesenchymal stromal cells (MSCs) and biomechanical support can often enhance the reparative reaction at the pre‐collapse stages of ONFH in patients and animal models .…”
Section: Discussionmentioning
confidence: 99%
“…Glucocorticoid (GC) use and alcoholism are associated with avascular necrosis (AVN) of the femoral head, 50% of which leads to collapse and joint destruction within 3 years of diagnosis . The common pathway for ONFH involves interruption of blood supply to the bone, resulting in osteocyte apoptosis and loss of structural integrity, ultimately leading to femoral head collapse . The transplantation of mesenchymal stromal cells (MSCs) and biomechanical support can often enhance the reparative reaction at the pre‐collapse stages of ONFH in patients and animal models .…”
Section: Discussionmentioning
confidence: 99%
“…Fat embolism and coagulation disorders are two of the most common causes of interrupted blood supply. GCs could directly or indirectly lead to hypofibrinolysis and thrombophilia, dysfunction and apoptosis of endothelial cells, lipid metabolism alterations, and platelet activation, which are followed by poor blood flow, ischemia, and eventually, osteonecrosis [30][31][32][33]. Nevertheless, the effectiveness of GCs differs among individuals owing to varied GC sensitivity [34].…”
Section: Discussionmentioning
confidence: 99%
“…endothelial cell damage, intravascular coagulation and disordered angiogenesis lead to ischemia, which is considered to be one of the core pathological results of onFH (20,22). Endothelial cell tube formation is the first step in neovascularization (65), and blood vessels are critical in bone remodeling because they supply nutrients (66).…”
Section: Circrnas and Vascular Endothelial Cellsmentioning
confidence: 99%
“…The mechanism by which onFH develops remains unclear (19). The majority of experts agree that a lack of blood supply to the femoral head and bone marrow causes death of osteocytes, as explained by the microvascular injury theory, osteoporosis theory, apoptosis theory, osteogenic enhancement and adipogenic weakening theory of bone marrow mesenchymal stem cells (20)(21)(22)(23)(24). it has previously been reported that numerous circrnas are associated with onFH, which suggested that they may have a critical role in the development and progression of onFH (25).…”
Section: Introductionmentioning
confidence: 99%